The Effect of the 5555 Strategy on Developing Productive Thinking among Fourth-Year Literary Students in History (Journal of the College of Basic Education, 2026)
The current research aims to reveal (the effect of the 5555 strategy on developing productive thinking among fourth grade literary students( To verify the aim and hypotheses of the research, a sample of students in the fourth literary grade at Al-Farouq High School, affiliated with the General Directorate of Education in Kirkuk, was selected. Two sections of the fourth literary grade, experimental and control, were selected.The research sample consisted of (47) students, who were divided into two groups: the experimental group, which included (24) students, and the control group, which included (23) students.Regarding research requirements, the researcher identified the subject matter to be applied, formulated behavioral objectives precisely, and prepared a number of specific teaching plans for each group. These requirements were also presented to a committee of experts and specialists for their scholarly opinions. Based on their comments, the necessary modifications were made to ensure the design was sound and appropriate for the desired objectives.The data were processed statistically using methods appropriate to the nature of the study, and the results revealed a statistically significant superiority in favor of the experimental group, indicating the effectiveness of the experimental treatment used.